Exfoliated bentonite/alginate nanocomposite hydrogel enhances intestinal delivery of probiotics by resistance to gastric pH and on-demand disintegration. (15th November 2021) - Kim, Jihyun; Hlaing, Shwe Phyu; Lee, Juho; Saparbayeva, Aruzhan; Kim, Sangsik; Hwang, Dong Soo; Lee, Eun Hee; Yoon, In-Soo; Yun, Hwayoung; Kim, Min-Soo; Moon, Hyung Ryong; Jung, Yunjin; et al.
Abstract: In this study, we developed Lactobacillus rhamnosus GG (LGG)-encapsulating exfoliated bentonite/alginate nanocomposite hydrogels for protecting probiotics by delaying gastric fluid penetration into the nanocomposite and their on-demand release in the intestine. The pore size of the bentonite/alginate nanocomposite hydrogels (BA15) was two-fold smaller than that of alginate hydrogel (BA00). Following gastric pH challenge, the survival of LGG in BA15 decreased by only 1.43 log CFU/g as compared to the 6.25 log CFU/g decrease in alginate (BA00). Further, the internal pH of BA15 decreased more gradually than that of BA00. After oral administration in mice, BA15 maintained shape integrity during gastric passage, followed by appropriate disintegration within the target intestinal area. Additionally, a fecal recovery experiment in mice showed that the viable counts of LGG in BA15 were six-fold higher than those in BA00. The findings suggest the exfoliated bentonite/alginate nanocomposite hydrogel as a promising platform for intestinal delivery of probiotics. Graphical abstract: Unlabelled Image Highlights: LGG was encapsulated in exfoliated bentonite/alginate nanocomposite hydrogels. Improved hydrogel pore size dramatically enhanced LGG survival at gastric pH. Complete intestinal release of LGG was observed after hydrogel disintegration. Fecal recovery of bentonite/alginate LGG was 6-fold greater than of alginate LGG.